2001
DOI: 10.1001/jama.285.18.2339
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term Effects of an Early Childhood Intervention on Educational Achievement and Juvenile Arrest

Abstract: Participation in an established early childhood intervention for low-income children was associated with better educational and social outcomes up to age 20 years. These findings are among the strongest evidence that established programs administered through public schools can promote children's long-term success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
404
0
15

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 648 publications
(433 citation statements)
references
References 28 publications
14
404
0
15
Order By: Relevance
“…There were surprisingly few racial/ethnic differences in sex risk behaviors. Yet, because of the disproportionate numbers of African Americans who cycle through correctional facilites, 79,80 the pediatrics community must focus on implementing culturally appropriate interventions for African American youth and young adults. More than any other racial/ethnic group, African Americans are disproportionately incarcerated and affected by HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…There were surprisingly few racial/ethnic differences in sex risk behaviors. Yet, because of the disproportionate numbers of African Americans who cycle through correctional facilites, 79,80 the pediatrics community must focus on implementing culturally appropriate interventions for African American youth and young adults. More than any other racial/ethnic group, African Americans are disproportionately incarcerated and affected by HIV/AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…All other interventions targeted both parents and children to simultaneously enhance protection and reduce family and individual risks. Examples include enhanced education services for primarily low-income, very young children to improve their cognitive, language, and socialcognitive skills; [48][49][50] and interventions that strengthen parenting skills, parent-child communication, and affective relationships. These include universal (eg, the Strengthening Families Program for Parents and Youth 10-14 28,72,73 and the Computer-Based Intervention 54,55 ), selective (eg, the New Beginnings Program 56 ), and indicated programmes (eg, Functional Family Therapy 74 ).…”
Section: The Science Of Preventionmentioning
confidence: 99%
“…Some researches indicate that school readiness is associated with learning, attending to school, developing further skills and academic success or failure (Jaramillo & Tietjen, 2001;Pianta & McCoy 1997;Reynolds 2001;Rouse, Brooks-Gunn, & Mclanahan, 2005 obtained from applications showed that children develop a positive attitude towards school and their academic skills increase (Liddell & Rae, 2001;Stith, Gorman, & Choudhury 2003;Nonoyama, Tarumi, & Bredenberg, 2009).…”
Section: Introductionmentioning
confidence: 99%